Spring Ichthyoplankton Assemblage Structure in the Yangtze Estuary Under Environmental Factors - Wang, Yibang; Liang, Cui; Chen, Zhaomin; Liu, Shude; Zhang, Hui; Xian, Weiwei (Frontiers in Marine Science, 2021)
Estuaries, where fresh and salty water converge, provide abundant nutrients for ichthyoplankton. Ichthyoplankton, including fish eggs, larvae, and juveniles, are important fishery recruitment resources. The Yangtze Estuary and its adjacent waters comprise a typical large-scale estuary and supply many important fish spawning, feeding, and breeding areas. In this study, 1,291 ichthyoplankton individuals were collected in the Yangtze Estuary in spring, from 2013 to 2020. The aims of the study were to provide detailed information on characteristics of the ichthyoplankton assemblage, explore interannual variation, and evaluate the effects of environmental variables on the temporal variation in assemblage structure. Twenty-six species in seventeen families were identified. The dominant species were Coilia mystus, Chelidonichthys spinosus, Engraulis japonicus, Hypoatherina valenciennei, Larimichthys polyactis, Salanx ariakensis, Stolephorus commersonnii, and Trachidermus fasciatus. The ichthyoplankton assemblage changed significantly over time, and Chelidonichthys spinosus became one of the dominant species. Canonical correspondence analysis showed that temperature and chlorophyll a were the key factors affecting the assemblage structure in the Yangtze Estuary in spring.